Efectos de los Efluentes Líquidos de la Curtiembre Inversiones Junio S.A.C. en la sensibilidad de Poecillía reticulata Guppy - Vásquez Aguilar, Jessica Karen (2019)
ABSTRACT In the present investigation the toxicological impact of the Inversiones Junior tannery effluents on Poecilia reticulata “Guppy” was determined by means of a short duration test. For the species Poecilia reticulata “Guppy”, the percentage of mortality and sublethal responses were evaluated. An average value of LC50 (mean lethal concentration) of 4,87 was found; average value of UT (toxic units) of 21,65; and an average ICOTOX value of 1,54. Likewise, the Chi2 analysis allowed us to affirm that there are no significant differences (Chi2 calculated> Chi2 tabulated) between the different replicas of the treatments; being found that the values of the concentrations were in the range of 0,098 to 0,376. Finally, it could be indicated that the effect of liquid effluents from Inversiones Junior tannery were very toxic in the sensitivity of Poecillia reticulata “Guppy”; generating a high mortality (between 70% and 74%).